Characteristics of an Effective University Professor From Students’ Perspective: Are the Qualities Changing? - Nushi, Musa; Momeni, Ali; Roshanbin, Maryam (Frontiers in Education, 2022)
This study investigates the characteristics of an effective university professor based on the evaluations made by students in different majors at a state university in Iran. Two-hundred forty BA, MA, and PhD students’ evaluations of their teachers were selected via purposive sampling. The evaluations were then content analyzed to determine which characteristics build the profile of an effective teacher in the students’ eyes. The results confirmed the findings of many previous studies that a good university professor needs to possess certain essential qualities. However, the profile of an effective university professor, at least the importance of the qualities that make up this profile, was rather different. More specifically, the most important criterion for evaluating the teachers was their assessment policies and practices. Furthermore, the findings suggest that the characteristics of an effective professor are dynamic and open to contextual, cultural and temporal influences. In light of the results of this study, it is recommended that higher education institutions put in place programs that educate teachers about a more learner-centered pedagogy to maximize not only their own teaching efficacy but also their students’ motivation and learning.